Pengaruh Karakteristik Individu dan Karakteristik Pekerjaan Terhadap Kinerja Pegawai Pada Dinas Dikpora Kabupaten Bima - Nabila Nabila; Mistar Mistar (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
This study aims to determine the effect of individual characteristics and job characteristics on employee performance partially at the Department of Youth and Sports of Bima Regency, the type of research used is associative research. 48 civil servants, 10 honorary people and 19 volunteers. The sample in this study were as many as 65 people. The sampling technique used was simple random sampling with the Slovin formula. Data collection techniques in this study are observation, questionnaire sharing in the form of questionnaires and literature study to find the latest and related references related to the title of this article, data analysis used is validity, reliability, classical assumptions, multiple linear regression, correlation coefficient test and determination, partial test and simultaneous test. The results in this study indicate that the variable individual characteristics and job characteristics together have an influence on the performance of employees at the Department of Education and Sport, Bima Regency.